If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 4q = 11 + 3q Solving 9 + 4q = 11 + 3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3q' to each side of the equation. 9 + 4q + -3q = 11 + 3q + -3q Combine like terms: 4q + -3q = 1q 9 + 1q = 11 + 3q + -3q Combine like terms: 3q + -3q = 0 9 + 1q = 11 + 0 9 + 1q = 11 Add '-9' to each side of the equation. 9 + -9 + 1q = 11 + -9 Combine like terms: 9 + -9 = 0 0 + 1q = 11 + -9 1q = 11 + -9 Combine like terms: 11 + -9 = 2 1q = 2 Divide each side by '1'. q = 2 Simplifying q = 2
| (-3u/v^3)^2 | | (2-a)(5z-7)=0 | | x/3-4=x-7 | | -4a+2=4a+82 | | e/-6=4 | | -7x+10=-3x+22 | | (72-x)=180 | | 5[7-5(-2x-9)]=50x+260 | | 6-2z=2z-10 | | (4x+32)=180 | | 20-1/10d=16 | | 5y+140=7x | | 22.27/x=4.16 | | 3x+2x^2-8x+6x^2= | | 22.27*x=4.16 | | x+22=34 | | 15=2x+10 | | x+22=33 | | 22.27*x=22.27 | | -2e^3x+19=3 | | 5y=7x-140 | | -x^2+6x=-1 | | 154/22 | | 11-3h+9=-8 | | 4x+1=2x+29 | | 3x-4=5x+9 | | https://www.mhcitts.com/images/test/53_1_8s.jpg | | 3x-7=6x-2 | | 165x+2771=7721 | | 2x(-5)=6x^2-11x | | 4/5x-3/4y=-10 | | 11+3h+9=-8 |